2011
DOI: 10.1074/jbc.m111.227694
|View full text |Cite
|
Sign up to set email alerts
|

MAPK Scaffold IQGAP1 Binds the EGF Receptor and Modulates Its Activation

Abstract: Cellular responses produced by EGF are mediated through the receptor (EGFR) and by various enzymes and scaffolds. Recent studies document IQGAP1 as a scaffold for the MAPK cascade, binding directly to B-Raf, MEK, and ERK and regulating their activation in response to EGF. We previously showed that EGF is unable to activate B-Raf in cells lacking IQGAP1. However, the mechanism by which IQGAP1 links B-Raf to EGFR was unknown. Here we report that endogenous EGFR and IQGAP1 co-localize and co-immunoprecipitate in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
98
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 85 publications
(111 citation statements)
references
References 62 publications
(52 reference statements)
1
98
0
Order By: Relevance
“…The effects of ligand binding on the interaction of receptors with IQGAP1 are diverse. For example, EGF has no effect on the association between IQGAP1 and epidermal growth factor receptor (17). By contrast, stimulation of Madin-Darby bovine kidney cells with FGF2 promotes binding of fibroblast growth factor recep-FIGURE 7.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The effects of ligand binding on the interaction of receptors with IQGAP1 are diverse. For example, EGF has no effect on the association between IQGAP1 and epidermal growth factor receptor (17). By contrast, stimulation of Madin-Darby bovine kidney cells with FGF2 promotes binding of fibroblast growth factor recep-FIGURE 7.…”
Section: Discussionmentioning
confidence: 99%
“…For example, IQGAP1 binds to several components of the epidermal growth factor receptorRaf-MAPK cascade, regulating activation of ERK (13,17,28). Work from a number of groups has demonstrated that IQGAP1 associates with selected transmembrane receptors and participates in their normal function (13,14).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The binding of CaM has been reported to inhibit the interaction of IQGAP1 with F-actin (20) as well as with Cdc42 (24,25) and B-Raf (26). Recent results further indicate that IQGAP1 co-immunoprecipitates with EGFR in a calmodulinsensitive fashion (27), and that the S100 protein also regulates IQGAP1 by binding to its IQ domains (28).…”
mentioning
confidence: 99%